Determinación de la incidencia de Toxoplasma gondii en felinos en la ciudad de Guayaquil sector “Cisne ll”. - Robles Chele, Clara Olaya (2023)
Toxoplasmosis is a zoonosis caused by protozoan parasites, according to epidemiology it is very common in the world and originated in South America and has now spread to all continents, this disease affects many warm-blooded animals including the cat as definitive host, livestock, birds and even humans. The purpose of this research is to determine the presence of Toxoplasma gondii in domestic and feral cats in the city of Guayaquil, Febres lamb parish, "swan II" sector through the deworming campaign that was carried out through direct smears, which is a sampling fecal and is collected from the animal's rectum with a swab, also the simple flotation for this test containers were given to the animal owners so that they could collect the feces of their pets, once the samples were collected they were kept in the refrigerator until they are sent in a cooler to the Bulldog Veterinary Laboratory, for this test fecal saturated water was used in a test tube after sampling, both tests are performed on a slide covered with a cover sheet, which is placed under a microscope and each animal is analyzed. The number of cats selected for the study was 100, the cats were chosen differently, that is, races, ages and sex. Once the samples were sent and processed in the Laboratory, data on the prevalence of toxoplasmosis were obtained; Of a total of 100 samples, we have that 10% of cats were positive for toxoplasmosis, which represents 0% of the total sample, it is a significant amount. Followed by 100% cats that have negative results. According to the statistics by age we have three groups of 1-11 months, 1-2 years, 3-4 years and 5 to 6 years of which there are 0%. By sex we have that females and males have 0% prevalence in toxoplasmosis gondii. By Persian, Siamese, mestizo and ocelot race we have 0% prevalence.